Association between buprenorphine/naloxone and high-dose opioid analgesic prescribing in Kentucky, 2012–2017. (1st December 2019) - Luu, Huong; Slavova, Svetla; Freeman, Patricia R.; Lofwall, Michelle; Browning, Steven; Slade, Emily; Bush, Heather
Highlights: Significant upward buprenorphine/naloxone prescribing trend in Kentucky, 2012–2017. Significant downward trend in high-dose opioid prescribing in Kentucky, 2012–2017. Significant opioid and buprenorphine/naloxone prescribing reciprocal relationship. Abstract: Introduction: Buprenorphine/naloxone treatment is a highly effective treatment for opioid use disorder decreasing illicit opioid use and both all-cause and opioid-involved overdose mortality. The purpose of this study was to investigate the relationships between buprenorphine/naloxone prescribing and high-dose opioid analgesic prescribing (HDOAP) over time. Methods: This longitudinal study used 2012–2017 Kentucky All Schedule Prescription Electronic Reporting data and cross-lagged structural equation analysis. For each quarter-county observation, HDOAP rate (per 1, 000 residents with opioid analgesic prescriptions) was used to predict buprenorphine/naloxone prescribing rate at the next quarter, and simultaneously buprenorphine/naloxone prescribing rate was used to predict HDOAP at the next quarter, accounting for baseline socioeconomic status, medical needs for opioid analgesics, and heroin availability. Results: On average, HDOAP rates in Kentucky decreased by more than 10% (p < .0001) and buprenorphine/naloxone prescribing rates increased by more than 5% (p < .0001) per quarter over the study period. Every one-per-thousand higher HDOAP rate in an earlier quarter was associated with a 0.01/1, 000 increase in the buprenorphine/naloxone prescribing rate in a later quarter (p = .009). Conversely, a one-unit higher buprenorphine/naloxone prescribing rate in an earlier quarter was associated with a 0.01/1, 000 reduction in the HDOAP rate in a subsequent quarter (p = .017). Conclusions: Our results indicate a significant reciprocal relationship between HDOAP and buprenorphine/naloxone prescribing and a clinically meaningful effect of buprenorphine/naloxone prescribing on reducing HDOAP. Future studies on buprenorphine/naloxone treatment expansion should take into account this bi-directional association in the context of longitudinal data and evaluate for public health benefits beyond the reduction of HDOAP.